Enterprise Social Software Platforms and Team Improvisation. Issue 3 (2nd July 2020) - Sun, Yuan; Wu, Lixia; Chen, Rui; Lin, Kuikui; Shang, Rong-An
ABSTRACT: Enterprise social software platforms (ESSPs) have emerged as an important infrastructure that enables teams to perform in the turbulent business environment. The current study adds to the scanty literature on ESSP by revealing and confirming the underlying mechanisms through which ESSP contributes to a team's ability to improvise. By surveying current ESSP users, we find that ESSP exercises its effect on team improvisation ability through team social capital as an important mediator. However, our results confirm the existence of two distinctive mediation mechanisms. First, intra-team ESSP use shapes improvisation ability through a team's internal bonding social capital partially, whereas inter-team ESSP use contributes to improvisation ability through external bonding social capital fully. Second, intra-team (not inter-team) ESSP use casts an additional impact on improvisation ability through within-team (not outside-team) bridging social capital; however, this mediation effect exists only among teams that are equipped with a high level of absorptive capacity. Therefore, the current research sheds new lights on the ESSP and contributes to the research on information technology–assisted team improvisation. Our findings also inform practitioners in leveraging ESSP for enhancement of the improvisation ability of teams in the workplace.